Communication about sexual health and decision making with adolescents in foster care - Pilgrim, Sarah (My University, 2014)
This study uses original data to identify predictors of communication between child welfare workers in a Midwestern state and the adolescents they serve who are residing in foster care regarding their sexual health and decision making. Quantitative analysis was used to identify statistically significant models of communication between child welfare workers and adolescents residing in foster care regarding their sexual health and decision making. The comfort level of child welfare workers around discussing sexual health issues with adolescents residing in foster care was found to be a significant predictor in five out of six regression models.
Keywords: Sexual health; Adolescents; Foster care; Quantitative analysis; Decision making